Management of Inoculation with Bradyrhizobium japonicum and Application of Vitamins for Hydroponic Soybean Cultivation - Alexandre H. de F. Lima; Josiane S. Salles; Eduardo P. Vendruscolo; Cássio de C. Seron; Rogério S. de Freitas; Sebastião F. de Lima; Gabriela R. Sant’Ana; Edilson Costa (International Journal of Microbiology)
The exchange of technologies used in field cultivation for hydroponic systems can potentially increase plant development and grain production, requiring studies to verify the best management forms, such as growth-promoting bacteria and biostimulant compounds. With this in mind, the study aimed to evaluate the effect of the application of thiamine and niacin, alone and combined, to soybean plants in the absence and presence of inoculation with B. japonicum on the agronomic and physiological characteristics of the crop grown in an ebb and flow hydroponic system. Eight treatments were evaluated using t-test (LSD) and Tukey’s test, both at 5% probability (P<0.05), in addition to Pearson correlation and canonical variables. The treatments consist of inoculation with B. japonicum at 1 mL 500 g−1 seeds (with and without) and foliar application of four solutions (water, niacin (0.1 g·L−1), thiamine (0.1 g·L−1), and niacin + thiamine (0.05 g·L−1 + 0.05 g·L−1)). We found that inoculation significantly improved the parameters evaluated and resulted in a gain of approximately 84.8% in yield when compared by t-test (P<0.05). In addition, the action of the vitamins was more significant when they were applied without the presence of B. japonicum, especially niacin, either alone or combined with thiamine, which increased yield parameters in this condition, identified when the Tukey’s test (P<0.05) was applied. We conclude that inoculation with Bradyrhizobium japonicum in soybean seeds grown in a hydroponic system significantly benefits the development and grain yield, mainly when combined with vitamin solutions. Niacin also has the potential to be used alone or combined with thiamine in noninoculated or inoculated hydroponic soybean crops, respectively.